2014
DOI: 10.1088/1758-5082/6/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

Direct 3D powder printing of biphasic calcium phosphate scaffolds for substitution of complex bone defects

Abstract: The 3D printing technique based on cement powders is an excellent method for the fabrication of individual and complex bone substitutes even in the case of large defects. The outstanding bone remodeling capacity of biphasic calcium phosphates (BCPs) containing hydroxyapatite (HA) as well as tricalcium phosphate (TCP) in varying ratios makes the adaption of powder systems resulting in BCP materials to this fabrication technique a desirable aim. This study presents the synthesis and characterization of a novel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 73 publications
(96 reference statements)
3
154
0
Order By: Relevance
“…29 Due to their excellent biocompatibility and osteoconductivity, CaP ceramic powders, with acid binders such as phosphoric acid / citric acid, are used widely in bone tissue engineering. 13,14,23,30 There are two main approaches to using ceramic powders in the context of 3DP. In the first approach, sacrificial polymeric binders (that pyrolyze upon sintering) 19 are used to improve green strength.…”
Section: Jariwala Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…29 Due to their excellent biocompatibility and osteoconductivity, CaP ceramic powders, with acid binders such as phosphoric acid / citric acid, are used widely in bone tissue engineering. 13,14,23,30 There are two main approaches to using ceramic powders in the context of 3DP. In the first approach, sacrificial polymeric binders (that pyrolyze upon sintering) 19 are used to improve green strength.…”
Section: Jariwala Et Almentioning
confidence: 99%
“…Castilho et al 23 fabricated 3D biphasic CaP (BCP) scaffolds using a hydraulic setting reaction of HA -TCP powders incorporating phosphoric acid and posttreatment with polylactic -co -glycolic acid solution. They demonstrated that osteoblastic MG63 cell proliferation was greater on BCP composites compared to pure HA or TCP scaffolds.…”
Section: In Vitro and In Vivo Testing Of 3dp Bone Scaffoldsmentioning
confidence: 99%
“…The technique of 3D printing consists of applying a layer of powder onto a surface and using an inkjet printer head to precisely spray the surface with a binder to bind the powder particles. The process is repeated by spreading a new layer of powder on top of the previous layer that results in the creation of a 3D structure [8,[21][22][23][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Along with their development in 3D printers, hydrogels can now be printed on any desired substrates free from nozzle clogging. 43 In general, a volume range between 1-100 pL of liquid droplets can escape from the nozzle by a pulse generated at the nozzle orifice. The advantage of 3D printing is in the direct writing of biomaterials and providing inexpensive way for manufacturing devices.…”
Section: D Printing Technologymentioning
confidence: 99%